Increased IL‐6 Expression in Osteoclasts Is Necessary But Not Sufficient for the Development of Paget's Disease of Bone. (June 2014) - Teramachi, Jumpei; Zhou, Hua; Subler, Mark A; Kitagawa, Yukiko; Galson, Deborah L; Dempster, David W; Windle, Jolene J; Kurihara, Noriyoshi; Roodman, G David
ABSTRACT Measles virus nucleocapsid protein (MVNP) expression in osteoclasts (OCLs) and mutation of the SQSTM1 (p62) gene contribute to the increased OCL activity in Paget's disease (PD). OCLs expressing MVNP display many of the features of PD OCLs. Interleukin‐6 (IL‐6) production is essential for the pagetic phenotype, because transgenic mice with MVNP targeted to OCLs develop pagetic OCLs and lesions, but this phenotype is absent when MVNP mice are bred to IL‐6–/– mice. In contrast, mutant p62 expression in OCL precursors promotes receptor activator of NF‐κB ligand (RANKL) hyperresponsivity and increased OCL production, but OCLs that form have normal morphology, are not hyperresponsive to 1, 25‐dihydroxyvitamin D3 (1, 25‐(OH)2D3), nor produce elevated levels of IL‐6. We previously generated p62P394L knock‐in mice (p62KI) and found that although OCL numbers were increased, the mice did not develop pagetic lesions. However, mice expressing both MVNP and p62KI developed more exuberant pagetic lesions than mice expressing MVNP alone. To examine the role of elevated IL‐6 in PD and determine if MVNP mediates its effects primarily through elevation of IL‐6, we generated transgenic mice that overexpress IL‐6 driven by the tartrate‐resistant acid phosphatase (TRAP) promoter (TIL‐6 mice) and produce IL‐6 at levels comparable to MVNP mice. These were crossed with p62KI mice to determine whether IL‐6 overexpression cooperates with mutant p62 to produce pagetic lesions. OCL precursors from p62KI/TIL‐6 mice formed greater numbers of OCLs than either p62KI or TIL‐6 OCL precursors in response to 1, 25‐(OH)2D3. Histomorphometric analysis of bones from p62KI/TIL‐6 mice revealed increased OCL numbers per bone surface area compared to wild‐type (WT) mice. However, micro‐quantitative CT (µQCT) analysis did not reveal significant differences between p62KI/TIL‐6 and WT mice, and no pagetic OCLs or lesions were detected in vivo. Thus, increased IL‐6 expression in OCLs from p62KI mice contributes to increased responsivity to 1, 25‐(OH)2D3 and increased OCL numbers, but is not sufficient to induce Paget's‐like OCLs or bone lesions in vivo. © 2014 American Society for Bone and Mineral Research.